益气活血方基于miR-124调控Wnt通路促进神经再生 (Nan Fang Yi Ke Da Xue Xue Bao, 2017)
OBJECTIVE: To investigate the effect of Yiqihuoxue prescription (NLXT) on nerve regeneration in MCAO-R rat models of qi deficiency and blood stasis syndrome and explore the underlying mechanisms. METHODS: The rats were randomized into 4 groups, namely the control group, model group, NLXT group and TXL group. The rats in NLXT group and TXL group were treated with gavage of NLXT and TXL solutions, respectively. The NFDS, QDSS and BSSS of the rats were evaluated. The regional cerebral blood flow (rCBF) were dynamically monitored with laser Doppler scanning, and the volume of cerebral infarction was detected with TTC-dye; the expression levels of nestin and BrdU were assayed with immunohistochemistry and mmunofluorescent staining. The expressions of miRNA-124, Wnt3a, GSK3β and β-catenin in the rat brain tissue were detected with PCR or Western blotting. RESULTS: NLXT and TXL both improved the neurological functions of the model rats, reduced NFDS, QDSS, and BSSS scores, decreased the volume of cerebral infarction, and promoted the recovery of the rCBF (P < 0.01). Nestin and BrdU expression levels were significantly increased in the rat brain tissue in NLXT group and TXL group. NLXT significantly inhibited high expressions of miRNA-124 and Wnt3a in response to stress, and increased β-catenin expression level (P < 0.01). NLXT and TXL produced no obvious effect on GSK3β expression in the model rats (P>0.05). CONCLUSION: NLXT can activate Wnt signaling by affecting miRNA-124 expression to offer neuroprotection and promote nerve regeneration in rats with cerebral ischemia with qi deficiency and blood stasis syndrome.